Effects of Amino Acid Decarboxylase Genes and pH on the Amine Formation of Enteric Bacteria From Chinese Traditional Fermented Fish (Suan Yu) - Yang, Qin; Meng, Ju; Zhang, Wei; Liu, Lu; He, Laping; Deng, Li; Zeng, Xuefeng; Ye, Chun (Frontiers in Microbiology, 2020)
The formation of biogenic amines (BAs) are important potential risks in Suan yu. This study investigated the amine production abilities of 97 strains of enteric bacteria screened from Suan yu. The genotypic diversity of amino acid decarboxylase and the effect of pH were explored on 27 strains of high-yield BAs. Results showed that high levels putrescine, histamine, and cadaverine were produced by the 97 strains. In addition, 27 strains carried odc, speA, speB, adiA, and ldc genes. 13 carried hdc gene. Morganella morganii strain 42C2 produced the highest putrescine content of 880 mg/L via the ornithine decarboxylase pathway. The highest histamine content was produced by K. aerogenes strain 13C2 (1869 mg/L). The highest cadaverine content was shown by Klebsiella pneumoniae strain 47C2 (1821 mg/L). The total BA content of the 27 strains reached the maximum at pH 4.5 (41423 mg/L) and the lowest at pH 6 (32586 mg/L). odc, adiA, speB, ldc, and hdc play important roles in the cellular acid stress response. Decarboxylase was strain specific rather than species specific. This study provides a reference for the genotypic diversity of decarboxylase and effect of pH on the types and abilities of BAs produced by enteric bacteria in Suan yu.